EKSPERIMENTASI MODEL PEMBELAJARAN APTITUDE TREATMENT INTRACTION (ATI) DENGAN PENDEKATAN CTL DITINJAU DARI KEDISIPLINAN BELAJAR MAHASISWA - Vera Dewi Susanti (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The purpose of this research are: (1) To know which learning model give better learning to result between ATI teaching model with CTL, ATI and conventional approach, (2) to know which gives better learning result among students who have discipline of high, medium and low (3) To know whether there is interaction between learning model and learning discipline to mathematics learning achievement.The type of research is quasi experimental research (quasi experimental). Instruments used were mathematics achievement test, questionnaire, and documentation instrument. The data were analyzed by using two-way variance analysis with unequal cells.The conclusions of this study are (1) Learning outcomes with ATI learning model with CTL approach is better than ATI and conventional model, while the ATI learning model is better than conventional. (2) Students' learning outcomes with higher learning discipline are better than those with moderate and low self-discipline, while students with discipline are better than those with low discipline. (3) There is no interaction between the learning model and the discipline of learning on mathematics learning achievement.